Neural ageing and synaptic plasticity: prioritizing brain health in healthy longevity - Navakkode, Sheeja; Kennedy, Brian K. (Frontiers in Aging Neuroscience, 2024)
Ageing is characterized by a gradual decline in the efficiency of physiological functions and increased vulnerability to diseases. Ageing affects the entire body, including physical, mental, and social well-being, but its impact on the brain and cognition can have a particularly significant effect on an individual's overall quality of life. Therefore, enhancing lifespan and physical health in longevity studies will be incomplete if cognitive ageing is over looked. Promoting successful cognitive ageing encompasses the objectives of mitigating cognitive decline, as well as simultaneously enhancing brain function and cognitive reserve. Studies in both humans and animal models indicate that cognitive decline related to normal ageing and age-associated brain disorders are more likely linked to changes in synaptic connections that form the basis of learning and memory. This activity-dependent synaptic plasticity reorganises the structure and function of neurons not only to adapt to new environments, but also to remain robust and stable over time. Therefore, understanding the neural mechanisms that are responsible for age-related cognitive decline becomes increasingly important. In this review, we explore the multifaceted aspects of healthy brain ageing with emphasis on synaptic plasticity, its adaptive mechanisms and the various factors affecting the decline in cognitive functions during ageing. We will also explore the dynamic brain and neuroplasticity, and the role of lifestyle in shaping neuronal plasticity.